2020
DOI: 10.7150/thno.39847
|View full text |Cite
|
Sign up to set email alerts
|

Rod-shape theranostic nanoparticles facilitate antiretroviral drug biodistribution and activity in human immunodeficiency virus susceptible cells and tissues

Abstract: Human immunodeficiency virus theranostics facilitates the development of long acting (LA) antiretroviral drugs (ARVs) by defining drug-particle cell depots. Optimal drug formulations are made possible based on precise particle composition, structure, shape and size. Through the creation of rod-shaped particles of defined sizes reflective of native LA drugs, theranostic probes can be deployed to measure particle-cell and tissue biodistribution, antiretroviral activities and drug retention.Methods: Herein, we cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 88 publications
0
19
0
1
Order By: Relevance
“…Bismuth- and sulfur-containing nanorods intrinsically radiolabeled with luteium 177 ( 177 LuBSNRs) can render both antiviral therapy and multimodal imaging. 224 The gold nanorods combined with the curcumin loaded poly (lactic- co -glycolic acid)- block -poly (ethylene glycol) (PLGA-b-PEG) copolymer are helpful for triggered and localized release of therapeutics along with photothermal capacity in one system. 225 The albumin-Bi 2 S 3 and magnetic nanoparticles can be developed for the combination of radiotherapy, magnetic hyperthermia, and chemotherapy.…”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
“…Bismuth- and sulfur-containing nanorods intrinsically radiolabeled with luteium 177 ( 177 LuBSNRs) can render both antiviral therapy and multimodal imaging. 224 The gold nanorods combined with the curcumin loaded poly (lactic- co -glycolic acid)- block -poly (ethylene glycol) (PLGA-b-PEG) copolymer are helpful for triggered and localized release of therapeutics along with photothermal capacity in one system. 225 The albumin-Bi 2 S 3 and magnetic nanoparticles can be developed for the combination of radiotherapy, magnetic hyperthermia, and chemotherapy.…”
Section: Nanotheranostics Perspectivementioning
confidence: 99%
“…Prior studies have demonstrated high RPV levels in kidney and gut exceeding those of spleen and liver 56 days after intramuscular dosing with poloxamer-encapsulated NRPV 19 . By contrast, intravenous co-dosing of bismuth-sulfate nanorods (BSNRs) with NRPV favored drug deposition in spleen and lymph node rather than kidney by four weeks post-injection 15 . Our findings recapitulate the notion that IV administration of NRPV enhances deposition in reticuloendothelial organs rather than those that facilitate drug excretion.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, theranostics serve as a bridge between therapeutic and diagnostic tracking. Previous iterations of HIV-1 theranostics included spherical europium cobalt-ferrite (CFEu) 14 and bismuth sulfide nanorods (BSNRs) 15 . These particles, loaded with RPV 14 , 15 or dolutegravir (DTG; an INSTI) 16 , showed characteristics of enhanced particle uptake in macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone is a potent anti-inflammatory corticosteroid and its nanoformuation is well known for the development of macrophages depot after intravenous and inhalation administration (Lammers et al 2020 ). The long-acting nanoformulation of anti HIV-1 drugs showed success as a macrophage-based drug carrier for anti-HIV-1 therapy compared to the free drug (Dash et al 2020 ; Kevadiya et al 2020 ; Kulkarni et al 2020 ; Mukadam et al 2020 ). Hence, this strategy might also work in COVID-19 treatment if alveolar macrophages targeting dexamethasone nanoparticles are designed ( Fig.…”
Section: Introductionmentioning
confidence: 99%